Conflict Management Education for Anesthesiology Residents: Bridging the Gap in Interpersonal and Communication Skills Competency. Issue 10 (1st October 2021) - Sinskey, Jina L.; Chang, Joyce M.; Thornton, Kevin C.; Boscardin, Christy K.; Sullivan, Kristina R.
Abstract : Supplemental Digital Content is available in the text. Abstract : Effective communication and conflict management are important skills for anesthesiologists and are designated by the Accreditation Council for Graduate Medical Education (ACGME) as elements of the "interpersonal and communication skill" competency (ACGME Anesthesiology Milestone Project 2020). However, structured conflict management education for anesthesiology residents remains limited. To address this gap, we developed and implemented a conflict management session incorporating didactics and application exercises using role-play and high-fidelity simulation (SIM) for anesthesiology residents (postgraduate years 3 and 4) at a tertiary academic medical institution. These sessions were well-received, and both role-play and SIM appear to help residents learn conflict management skills.